In situ anti-Staphylococcus aureus activities of ethanolic leaf extract of Rhodomyrtus tomentosa (Aiton) Hassk. in raw chilled pork - วิสุทธิ มณฑล; เอี่ยมโอษฐ์ อิงอร (Progress in Applied Science and Technology, 2018)
Ethanolic extract of Rhodomyrtus tomentosa leaf contained antibacterial activities against many Gram-positive pathogenic bacteria, including Staphylococcus aureus. This study investigated antibacterial effects on S. aureus using both n vitro and in situ assays. In vitro studies were determined by Time kill, Biofilm formation and colonial morphology detection. In situ assay was analyzed an anti-bacterial activity of the extract against S. aureus in chilled pork. Time-kill assay shown that the extract at a concentration of 4MIC (1.24 mg/ml) could reduce the number of S. aureus cells by 99.9% within 24 h. The ethanolic extract at more than or equal MIC concentration could prevent biofilm formation and inhibited slime and Staphyloxanthin production. In addition, the extract inhibited S. aureus growth in raw pork during storage at 10 ºC compared to control and 10% salt solution in 3 days of storage. The results of this study revealed that the extract of R. tomentosa could be an alternative preservative chemical compound to inhibit bacteria and may be employed in food preservation and pharmaceutical purposes.